The Holistic Approach to Academia: Traditional Classroom Instruction and Experiential Learning of Student-Athletes - Lisa Coffey; Armani Davis (MDPI AG, 2019)
National Collegiate Athletic Association (NCAA) student-athletes represent a unique subculture on college campuses, and the athlete must balance the rigors of coursework, athletics, and the non-traditional dynamics associated with being an athlete, which include “dumb jock” stereotypes, isolation, negative criticism, and the fear associated with athletic retirement. Unlike non-athletes, these students face increasing pressure from outside sources, including family, coaches, and fans, to be the best. However, participation in athletics gives student-athletes an opportunity to learn valuable skills and characteristics that are transferrable to the workplace. This mixed-method research extracted descriptive data to identify the characteristics learned through athletics, the skill-sets potential employers value the most, and how those skills are transferable to the workplace. Those characteristics include refined leadership, communication skills, and an ability to multi-task with a laser-sharp focus. Student-athletes are assertive, driven, understand the concept of teamwork, and handle constructive criticism without adverse reactions. The results show that when student-athletes engage in the classroom and absorb the learning opportunities provided through athletics, student-athletes can have a competitive advantage in the job marketplace.